Differential Expression of Steroid Hormone Receptors and Ten Eleven Translocation Proteins in Endometrial Cancer Cells - Mahajan, Vishakha; Gujral, Palak; Jain, Lekha; Ponnampalam, Anna P. (Frontiers in Oncology, 2022)
Steroid hormones govern the complex, cyclic changes of the endometrium, predominantly through their receptors. An interplay between steroid hormones and epigenetic mechanisms controls the dynamic endometrial gene regulation. Abnormalities in expression of genes and enzymes associated with steroid hormone signalling, contribute to a disturbed hormonal equilibrium. Limited evidence suggest the involvement of TET (Ten Eleven Translocation)-mediated DNA hydroxymethylation in endometrial cancer, with some data on the use of TET1 as a potential prognostic and diagnostic biomarker, however the mechanisms guiding it and its regulation remains unexplored. This study aims to explore the changes in the expressions of TETs and steroid hormone receptors in response to estrogen and progesterone in endometrial cancer cells. Gene expression was examined using real-time PCR and protein expression was quantified using fluorescent western blotting in endometrial cancer cell lines (AN3 and RL95-2). Results indicate that TET1 and TET3 gene and protein expression was cell-specific in cancer cell-lines. Protein expression of TET1 was downregulated in AN3 cells, while TET1 and TET3 expressions were both upregulated in RL95-2 cells in response to estrogen-progesterone. Further, a decreased AR expression in AN3 cells and an increased ERα and ERβ protein expressions in RL95-2 cells was seen in response to estrogen-progesterone. PR gene and protein expression was absent from both cancer cell-lines. Overall, results imply that expressions of steroid hormones, steroid-hormone receptors and TETs are co-regulated in endometrial cancer-cells. Further studies are needed to interpret how these mechanisms fit in with DNMTs and DNA methylation in regulating endometrial biology. Understanding the role of TETs and hydroxymethylation in steroid hormone receptor regulation is crucial to comprehend how these mechanisms work together in a broader context of epigenetics in the endometrium and its pathologies.